COMPARISON OF INDUCTIVE AND CAPACITIVE COUPLINGS USED TO CLOSE THE FEEDBACK LOOP USED IN SWITCH MODE POWER SUPPLIES (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
Switching mode power supplies are widely used to power various electronic equipment and are adaptable to technical requirements. Switching power supplies use average switching frequencies in the kHz-MHz range generated by the internal frequency generator. Switching mode power supplies use one or more feedback reaction loops to stabilize the parameters the connected load requires. We physically realized two switching power supplies using flyback topology to measure the parameters of the two types of couplings, inductive and capacitive. In this article, we presented a comparison of the parameters of the two reaction loops and an analysis of the two modules that make up the reaction loop.
Keywords: Capacitive coupling; Inductive coupling; Flyback; Switch mode power supply; Reaction loop